2010
DOI: 10.1016/j.procs.2010.04.197
|View full text |Cite
|
Sign up to set email alerts
|

Coupling visualization and data analysis for knowledge discovery from multi-dimensional scientific data

Abstract: Knowledge discovery from large and complex scientific data is a challenging task. With the ability to measure and simulate more processes at increasingly finer spatial and temporal scales, the growing number of data dimensions and data objects presents tremendous challenges for effective data analysis and data exploration methods and tools. The combination and close integration of methods from scientific visualization, information visualization, automated data analysis, and other enabling technologies —such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…This article combines literature measurement, visual analysis, social network analysis and other methods to analyze the status of cultural added value research [3][4][5] . The research ideas and technical route are shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…This article combines literature measurement, visual analysis, social network analysis and other methods to analyze the status of cultural added value research [3][4][5] . The research ideas and technical route are shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…VR takes advantage of the computer technological development and scientific visualization to create a virtual world [ 4 ]. The use of VR has become very popular because it offers a high level of realism and immersion but requires advanced computing technologies capable of processing large amounts of scientific data and graphics [ 5 ]. VR has been used in different areas such as engineering, medicine, education, entertainment, astronomy, archaeology, and arts.…”
Section: Introductionmentioning
confidence: 99%
“…Designers of multidimensional(MD) models must structure the information that is available into facts and dimensions. Facts are usually measures of business processes of some kind and dimensions represent the different ways in which the data can be viewed and sorted [3]. Business intelligence(BI) systems extend this by using heuristic and statistical models to find interesting features and make predictions.…”
Section: Introductionmentioning
confidence: 99%